2012
DOI: 10.1143/jjap.51.09ld15
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Study of Application of Piezoelectric Chiral Polymer to Actuator

Abstract: To realize a new piezoelectric chiral polymer actuator, we studied the motion induced by the shear piezoelectricity of a poly(L-lactic acid) (PLLA) film under the application of an ac voltage. First, PLLA was subjected to a supercritical CO2 treatment to change its high-order structure, resulting in an improvement in its piezoelectricity. Then, we designed a PLLA film roll transducer, which consisted of a piece of the treated PLLA film rolled into a long thin roll. To demonstrate the transducer, we placed it v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…However, the pyroelectric property of PVDF makes it possible to detect temperature signals, which may be confused with a pressure signal in E‐skin applications. As one of widely used piezoelectric polymers, poly( l ‐lactic acid) (PLLA) is synthesized by the polymerization of l ‐lactic acid monomers and it can be used for applications of actuators, smart fabric, and filtration devices 28–30. The piezoelectric polymer PLLA features a large number of CO double bonds with an angle of 125° relative to the main carbon chain, and the parallel dipole component of the CO dipoles can show polarity under shear stress 31,32.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pyroelectric property of PVDF makes it possible to detect temperature signals, which may be confused with a pressure signal in E‐skin applications. As one of widely used piezoelectric polymers, poly( l ‐lactic acid) (PLLA) is synthesized by the polymerization of l ‐lactic acid monomers and it can be used for applications of actuators, smart fabric, and filtration devices 28–30. The piezoelectric polymer PLLA features a large number of CO double bonds with an angle of 125° relative to the main carbon chain, and the parallel dipole component of the CO dipoles can show polarity under shear stress 31,32.…”
Section: Introductionmentioning
confidence: 99%
“…PLLA is more widely utilized for making piezoelectric devices while PDLA is often used as an agent to improve the piezoelectric and thermo-mechanical properties of PLLA. [35,[111][112][113][114] Compared with PVDF, PLLA exhibits a higher shear piezoelectric coefficient value (d 14 ) of ≈12 pm V −1 . [115] Studies have demonstrated that the chirality of the asymmetric carbon atoms in PLLA affects its shear piezoelectric constant.…”
Section: Pla-based Nanofibersmentioning
confidence: 99%
“…Due to its bio-resorption, low toxicity, degradation, biocompatibility and useful mechanical performance, its presence in the medical field continues to grow. PLA can exist as linear polyester stereoisomer forms, including (poly(L-lactic acid) (PLLA), poly(D-lactic acid) (PDLA) and poly(D,L-lactic acid) (PDLLA) [72,132]. PLLA has optical activity characteristics and PDLA exists as its optical isomer.…”
Section: Electroactive Polymersmentioning
confidence: 99%